1993
DOI: 10.1095/biolreprod49.3.604
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α Receptor Concentrations in Corpora Lutea of Cycling, Pregnant, and Pseudopregnant Pigs1

Abstract: The objective of this study was to measure and compare the concentrations of PGF 2 alpha receptors on luteal cells taken from cycling, pregnant, and pseudopregnant pigs. Corpora lutea were removed surgically from cycling, pregnant, and pseudopregnant (induced with 5 mg estradiol valerate/day i.m. beginning on Day 11) pigs on Days 12, 13, and 14 (postestrus) and were subjected to collagenase dissociation. Dissociated luteal cells (approximately 100,000 large viable cells per tube) were assayed for specific PGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…We also tested 11␤-PGF 2␣ because it has an affinity for the FP receptor equal to PGF 2␣ (20) and is a PGF synthase product of PGD 2 (40 was the only eicosanoid besides PGF 2␣ to produce an increase in protein content at 10 Ϫ8 M, and the increase produced by the two FP receptor-specific agonists at 10 Ϫ8 M was equal to that produced by 100-fold higher concentrations of PGD 2 , PGE 2 , and PGF 1␣ . These results support the assumption that the growth-stimulatory effects of PGD 2 , PGE 2 , and PGF 1␣ at 10 (41). The potency of PGF 2␣ as a stimulus for myocyte growth in comparison with other eicosanoids (Fig.…”
Section: Protein Synthesis Is Increased In Ventricular Myocytessupporting
confidence: 84%
See 1 more Smart Citation
“…We also tested 11␤-PGF 2␣ because it has an affinity for the FP receptor equal to PGF 2␣ (20) and is a PGF synthase product of PGD 2 (40 was the only eicosanoid besides PGF 2␣ to produce an increase in protein content at 10 Ϫ8 M, and the increase produced by the two FP receptor-specific agonists at 10 Ϫ8 M was equal to that produced by 100-fold higher concentrations of PGD 2 , PGE 2 , and PGF 1␣ . These results support the assumption that the growth-stimulatory effects of PGD 2 , PGE 2 , and PGF 1␣ at 10 (41). The potency of PGF 2␣ as a stimulus for myocyte growth in comparison with other eicosanoids (Fig.…”
Section: Protein Synthesis Is Increased In Ventricular Myocytessupporting
confidence: 84%
“…We found that PGF 2␣ stimulated the incorporation of [ 3 H]phenylalanine by cardiomyocytes at concentrations as low as 0.1 nM and obtained 50% of maximal stimulation at 11 nM. Our EC 50 value compares favorably with dissociation constants of 9 -47 nM for high affinity PGF 2␣ binding sites determined on luteal cells taken from cycling, pregnant, and pseudopregnant pigs (41) and the dissociation constant of 1.3 nM for COS cells transiently transfected with a murine FP receptor expression vector (20). In addition, our EC 50 (15) and agrees well with that calculated for phosphatidylinositol hydrolysis in transfected COS-1 cells (10 nM) (20).…”
Section: Discussionsupporting
confidence: 57%
“…These results are not in agreement with previous studies (Gadsby et al 1990, in which a decreased amount of PGF 2a binding sites was noted in luteal cells of pregnant and pseudopregnant pigs. It is worthwhile to mention that Gadsby et al (1990Gadsby et al ( , 1993 measured the capacity of [3H]PGF 2a binding to its membrane receptors in isolated porcine luteal cells. Thus, the observed discrepancy could result from the different animal models and methods used.…”
Section: Rescue Of Luteal Function During Early Pregnancymentioning
confidence: 99%
“…Although porcine CL abundantly express PGF2a receptors (PTGFR) in the early luteal phase [1,2], they remain insensitive to single treatment with exogenous PGF2a until Days 12 to 13 of the estrous cycle [3]. Interestingly, repeated injection of PGF2a on Day 5 of the estrous cycle induced luteolysis in pigs [4].…”
Section: Introductionmentioning
confidence: 99%